2019
DOI: 10.3390/en12112156
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Microgrid Energy Management Considering Flexible Energy Sources

Abstract: Aggregation of distributed generations (DGs) along with energy storage systems (ESSs) and controllable loads near power consumers has led to the concept of microgrids. However, the uncertain nature of renewable energy sources such as wind and photovoltaic generations, market prices and loads has led to difficulties in ensuring power quality and in balancing generation and consumption. To tackle these problems, microgrids should be managed by an energy management system (EMS) that facilitates the minimization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 92 publications
0
79
0
Order By: Relevance
“…In the last few years, several EMS approaches were investigated. For example, Shayeghi et al [25] classified EMSs as (i) nonrenewable based, (ii) energy storage system based, (iii) demand-side management based and (iv) hybrid system based. Instead, Dehghanpour et al [26] identified three different categories, namely centralized, distributed and hybrid control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the last few years, several EMS approaches were investigated. For example, Shayeghi et al [25] classified EMSs as (i) nonrenewable based, (ii) energy storage system based, (iii) demand-side management based and (iv) hybrid system based. Instead, Dehghanpour et al [26] identified three different categories, namely centralized, distributed and hybrid control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important aspect for optimal EMSs is uncertainty-in this case of the prediction profiles of available renewable energy and end-user consumption [19]. One common paradigm for handling uncertainty is robust optimization, which uses uncertainty sets and combines a worst-case analysis with min-max formulations to obtain optimal solutions that are robust against variations in a parameter with respect to a nominal value (optimal worst-case scenario) [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the development of strategic policies and regulations, such as market liberalization and decarbonization plans, that are stimulating the decommissioning of large fossil fuel-powered power plants, and the adoption of local measures for grid management [2,3] that are capable of better integrating the deployment of renewable sources. Therefore, the future power system requires the exploitation of the flexibility offered by all of the involved parties to obtain a reliable and cost-effective power supply [1,5,6]. However, a paradigmatic change of the power system operation from a top-down to a bottom-up approach implies a shift in responsibilities from centralized authorities towards decentralized entities, encouraging the interaction of all the grid users.…”
Section: Introductionmentioning
confidence: 99%